Maternity Benefits and Marital Stability after Birth: Evidence from the Soviet Baltic Republics - Elizabeth Brainerd; Olga Malkova (Institute of Labor Economics (IZA), 2023)
Can a policy intervention in the stressful first year after a birth affect marital stability? We examine this question using a large expansion in maternity benefits in 1982 in the Baltic countries of Estonia, Latvia and Lithuania. The program provided partially paid leave until the child's first birthday and included a small cash payment at birth. We use individual-level panel data and compare the Baltics with similar East European countries using a difference-indifferences framework. Maternity benefits decrease divorce within the first year after birth. This decrease persists for at least a decade, indicating that couples avoided divorce altogether rather than simply delaying it. While mothers extended their leave by several months, they returned to full-time work afterwards, consistent with egalitarian gender norms in the labor market.
Keywords: J12; J16; J18; P2; P3; 330; marriage; divorce; marital stability; maternity benefits; Baltics; Eastern Europe